Effects of flipped learning-based guitar instruction on motivation, attitude, and accompaniment skills - Hüseyin Yılmaz; Onur Zahal (Journal of Pedagogical Research, 2023)
The purpose of this research is to determine the effects of flipped learning-based guitar instruction on students' motivation, attitude, and accompaniment skills. This experimental study consisted of 26 students who were attending the lectures at Fine Arts Education Department of Music Teaching. A random sampling technique was employed to select 14 students for the experimental group and 12 students for the control group. Data collection tools used included instrument motivation scale, attitude scale towards instrument, and guitar accompaniment evaluation form. During the twelve-week intervention, both the control group and the experimental group trained for one hour each week. Students in the experimental group performed significantly higher accompaniment skills than students in the control group. The flipped learning model was found to be more effective than traditional learning method. Based on the results of the study, some recommendations were made for future studies.